Film coating method for surface of preservative film
By depositing a carbon transition layer, composite layer and fluorine layer on the surface of the plastic wrap, the problem of packaging oxidation caused by oxygen transmission is solved, and a better preservation effect and extended preservation time are achieved.
Patent Information
- Application Number
- CN202311248378.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing plastic wrap cannot effectively block low-molecular oxygen, causing the packaging to be oxidized and reduce the fresh preservation effect.
Magneto-controlled sputtering ion plating is used to deposit carbon transition layer, composite layer and fluorine layer on the surface of the plastic wrap to form a smooth and compact, non-lime-friendly protective film to prevent oxygen molecules from passing through.
It extends the fresh-keeping time, enhances the fresh-keeping effect, and avoids the packaging being oxidized.
Smart Images

Figure CN119685767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating, and in particular to a coating method for the surface of a fresh-keeping film. Background Art
[0002] At present, plastic wrap is used more and more widely in food, medical and other industries. It has the advantages of easy molding, light weight and low price. It can effectively isolate the packaged objects from the air and achieve a certain preservation effect.
[0003] However, low molecular weight oxygen can still penetrate the plastic wrap into the package, causing the packaged items to be oxidized, thereby reducing the preservation effect of the packaged items. Summary of the invention
[0004] The purpose of the embodiment of the present invention is to provide a coating method for the surface of a cling film, by vacuum coating the surface of the cling film so that the coated cling film has the characteristics of being smooth, firm, and non-lipophilic, oxygen molecules cannot penetrate the cling film, and oxidation of the packaged objects can be effectively avoided, thereby extending the preservation time and enhancing the preservation effect.
[0005] In order to achieve the above object, an embodiment of the present invention provides a coating method for the surface of a cling film, comprising:
[0006] A carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating;
[0007] Depositing a composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating;
[0008] Fluorine ions are doped on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer.
[0009] Furthermore, the method of depositing a carbon transition layer on the surface of the cling film by magnetron sputtering ion plating specifically includes:
[0010] Place the plastic wrap in the vacuum chamber and evacuate to a vacuum degree of 1.0×10 -3 Pa, and controlling the temperature in the vacuum chamber to be maintained at 20°C to 50°C;
[0011] Introducing argon gas into the vacuum chamber, and controlling the gas pressure in the vacuum chamber to be between 0.8 and 1.0 Pa;
[0012] The carbon target is turned on, and a carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating; wherein the current of the carbon target is 1.0-1.5A, the applied bias voltage is -150V, and the bias frequency is 180kHz.
[0013] Furthermore, the thickness of the carbon transition layer is 20 nm.
[0014] Furthermore, the method of depositing the composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating specifically includes:
[0015] The vacuum degree in the vacuum chamber was adjusted to 1.5×10 -3 Pa, nitrogen is introduced into the vacuum chamber, and the air pressure in the vacuum chamber is controlled at 0.5 Pa;
[0016] The titanium target and the carbon target are turned on, and a composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating; wherein the current of the titanium target is 0.5A, the current of the carbon target is 2.5A, the applied bias voltage is -150V, and the bias frequency is 120kHz.
[0017] Furthermore, the thickness of the composite layer is 10-15 nm.
[0018] Further, the step of doping fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer specifically includes:
[0019] The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, using carbon tetrafluoride as a doping gas, and adopting a zero bias doping method to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of the carbon tetrafluoride is 80sccm, the ion energy is 400eV, and the ion beam density is 100μA / cm 2 .
[0020] Furthermore, the doping time of the fluorine layer is 20 minutes.
[0021] Furthermore, the deposition rate of the fluorine layer is
[0022] Furthermore, the thickness of the fluorine layer is 5 nm.
[0023] Furthermore, the total thickness of the carbon transition layer, the composite layer and the fluorine layer is 20-50 nm.
[0024] Compared with the prior art, the embodiment of the present invention provides a coating method for the surface of a cling film, firstly, a carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating; then, a composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating; finally, fluorine ions are doped on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer. The embodiment of the present invention performs vacuum coating on the surface of the cling film, so that the coated cling film has the characteristics of being smooth, tight, and non-lipophilic, oxygen molecules cannot penetrate the cling film, and the packaged objects can be effectively prevented from being oxidized, thereby extending the preservation time and enhancing the preservation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a flow chart of a preferred embodiment of a coating method for the surface of a cling film provided by the present invention;
[0026] Figure 2 It is a structural schematic diagram of a preferred embodiment of a coated cling film provided by the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this technical field without creative work are within the scope of protection of the present invention.
[0028] The embodiment of the present invention provides a coating method for the surface of a cling film, see Figure 1 FIG. 1 is a flow chart of a preferred embodiment of a coating method for a cling film surface provided by the present invention, wherein the method comprises steps S11 to S13:
[0029] Step S11, depositing a carbon transition layer on the surface of the cling film by magnetron sputtering ion plating;
[0030] Step S12, depositing a composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating;
[0031] Step S13, doping fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer.
[0032] In the specific implementation, first, a carbon transition layer is deposited on the surface of the cling film by a magnetron sputtering ion plating method; then, a composite layer is deposited on the surface of the carbon transition layer by a magnetron sputtering ion plating method; finally, fluorine ions are doped on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer, and the hydrophobic and oleophobic properties of the protective film on the surface of the cling film are improved by the fluorine layer.
[0033] Combination Figure 2 Shown is a schematic structural diagram of a preferred embodiment of a coated cling film provided by the present invention. The surface of the cling film is coated by adopting the coating scheme provided by the embodiment of the present invention. The corresponding coated cling film is mainly composed of a cling film, a carbon transition layer, a composite layer and a fluorine layer, and the carbon transition layer is on the surface of the cling film, the composite layer is on the surface of the carbon transition layer, and the fluorine layer is on the surface of the composite layer.
[0034] In another preferred embodiment, the method of depositing the carbon transition layer on the surface of the cling film by magnetron sputtering ion plating specifically includes:
[0035] Place the plastic wrap in the vacuum chamber and evacuate to a vacuum degree of 1.0×10 -3 Pa, and controlling the temperature in the vacuum chamber to be maintained at 20°C to 50°C;
[0036] Introducing argon gas into the vacuum chamber, and controlling the gas pressure in the vacuum chamber to be between 0.8 and 1.0 Pa;
[0037] The carbon target is turned on, and a carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating; wherein the current of the carbon target is 1.0-1.5A, the applied bias voltage is -150V, and the bias frequency is 180kHz.
[0038] As a preferred solution, the thickness of the carbon transition layer is 20 nm.
[0039] Specifically, in combination with the above-mentioned embodiment, during the process of depositing the carbon transition layer on the surface of the cling film, the cling film can be placed in a vacuum chamber, and the vacuum chamber is evacuated to 1.0×10 -3 Pa or above, and the temperature in the vacuum chamber is controlled to be maintained in the range of 20°C to 50°C, and then argon gas (Ar, purity is 99.99%) is introduced into the vacuum chamber, and the air pressure in the vacuum chamber is controlled in the range of 0.8Pa to 1.0Pa, and then, the carbon target (C target) is turned on for sputtering, and under the conditions of the carbon target current of 1.0A to 1.5A, the applied bias voltage of -150V, and the bias frequency of 180kHz, a carbon transition layer is deposited on the surface of the plastic wrap by magnetron sputtering ion plating, and the thickness of the carbon transition layer is 20 nanometers.
[0040] For example, during the entire coating process of the cling film, the temperature in the vacuum chamber can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and can also be set according to actual needs, which is not specifically limited in the embodiments of the present invention.
[0041] For example, during the deposition of the carbon transition layer, the pressure in the vacuum chamber may be 0.8 Pa, 0.9 Pa or 1.0 Pa, and may also be set according to actual needs, which is not specifically limited in the embodiment of the present invention.
[0042] For example, during the deposition of the carbon transition layer, the carbon target current may be 1.0 A, 1.1 A, 1.2 A, 1.3 A, 1.4 A or 1.5 A, and may also be set according to actual needs, which is not specifically limited in the embodiment of the present invention.
[0043] In another preferred embodiment, the method of depositing the composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating specifically includes:
[0044] The vacuum degree in the vacuum chamber was adjusted to 1.5×10 -3 Pa, nitrogen is introduced into the vacuum chamber, and the air pressure in the vacuum chamber is controlled at 0.5 Pa;
[0045] The titanium target and the carbon target are turned on, and a composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating; wherein the current of the titanium target is 0.5A, the current of the carbon target is 2.5A, the applied bias voltage is -150V, and the bias frequency is 120kHz.
[0046] Specifically, in combination with the above-mentioned embodiment, during the process of depositing the composite layer on the surface of the carbon transition layer, the vacuum degree in the vacuum chamber can be adjusted to 1.5×10 -3 Pa or above, nitrogen (N2, purity of 99.99%) is introduced into the vacuum chamber, and the gas pressure in the vacuum chamber is controlled at 0.5Pa, and then, the titanium target (Ti target) and the carbon target (C target) are turned on for joint sputtering. Under the conditions that the current of the titanium target is 0.5A, the current of the carbon target is 2.5A, the applied bias is -150V, and the bias frequency is 120kHz, a magnetron sputtering ion plating method is used to deposit and form a composite layer on the surface of the carbon transition layer. Correspondingly, the composite layer is a Ti / DLC composite layer.
[0047] As a preferred solution, the thickness of the composite layer is 10-15 nm.
[0048] Specifically, in combination with the above-mentioned embodiment, the thickness of the composite layer deposited on the surface of the carbon transition layer is in the range of 10 nanometers to 15 nanometers.
[0049] Exemplarily, the thickness of the composite layer may be 10 nanometers, 11 nanometers, 12 nanometers, 13 nanometers, 14 nanometers or 15 nanometers, and may also be set according to actual needs, which is not specifically limited in the embodiment of the present invention.
[0050] In another preferred embodiment, the step of doping fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer specifically includes:
[0051] The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, using carbon tetrafluoride as a doping gas, and adopting a zero bias doping method to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of the carbon tetrafluoride is 80sccm, the ion energy is 400eV, and the ion beam density is 100μA / cm2 .
[0052] Specifically, in combination with the above-mentioned embodiment, during the process of depositing the fluorine layer on the surface of the composite layer, carbon tetrafluoride (CF4) can be introduced into the vacuum chamber, and carbon tetrafluoride is used as the doping gas. The vacuum degree in the vacuum chamber is 3.5×10 -4 Under the condition of Pa, fluorine ions are doped on the surface of the composite layer, and in order to avoid the etching of the deposited composite layer by the fluorine ions, fluorine is doped by zero bias doping to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of carbon tetrafluoride introduced is 80sccm, the ion energy is 400eV, and the ion beam density is 100μA / cm 2 .
[0053] As a preferred solution, the doping time of the fluorine layer is 20 minutes.
[0054] Specifically, in combination with the above embodiment, in the process of doping fluorine ions on the surface of the composite layer, the doping time of fluorine ions is 20 minutes.
[0055] As a preferred embodiment, the deposition rate of the fluorine layer is
[0056] Specifically, in combination with the above embodiment, in the process of doping fluorine ions on the surface of the composite layer, the deposition rate of fluorine ions is within the range.
[0057] For example, the deposition rate of fluoride ions can be or It can also be set according to actual needs, and the embodiment of the present invention does not make any specific limitation.
[0058] As a preferred solution, the thickness of the fluorine layer is 5 nm.
[0059] Specifically, in combination with the above embodiment, the thickness of the fluorine layer deposited on the surface of the composite layer is 5 nanometers.
[0060] In yet another preferred embodiment, the total thickness of the carbon transition layer, the composite layer and the fluorine layer is 20-50 nm.
[0061] Specifically, in combination with the above embodiments, the total thickness of the protective film (including the carbon transition layer, the composite layer and the fluorine layer) formed on the surface of the cling film is in the range of 20 nanometers to 50 nanometers. It can be understood that if the total thickness of the protective film is greater than this range, the protective film is relatively brittle and easily causes the film to fall off. If the total thickness of the protective film is less than this range, the protective film will be unevenly plated, affecting the coating effect.
[0062] It should be noted that the traditional coating method is generally carried out in a high temperature atmosphere area of 150°C to 350°C in a vacuum chamber, and plastic products (such as cling film) lack heat resistance and have a high expansion coefficient. When the processing temperature is above 200°C, a high adhesion cannot be obtained. Therefore, the traditional coating method has certain limitations on the coating object. The coating method provided in the embodiment of the present invention can keep the temperature in the vacuum chamber within the range of 20°C to 50°C during the entire coating process of the cling film, thereby realizing a coating method at room temperature.
[0063] In combination with all the above embodiments, the implementation process of the present solution is described below through the first specific embodiment, including: (1) placing a cling film in a vacuum chamber, controlling the temperature in the vacuum chamber to be maintained at 20°C, and evacuating the vacuum chamber to 1.0×10 -3 Pa or higher vacuum degree, then, introduce argon gas (Ar, purity is 99.99%) into the vacuum chamber, and control the pressure in the vacuum chamber at 0.8 Pa, turn on the carbon target for sputtering, and use magnetron sputtering ion plating method to deposit a carbon transition layer on the surface of the plastic wrap under the conditions of 1.0A current of the carbon target, -150V bias voltage applied, and 180kHz bias frequency; (2) adjust the vacuum degree in the vacuum chamber to 1.5×10 -3 Pa or more, nitrogen (N2, purity of 99.99%) is introduced into the vacuum chamber, and the pressure in the vacuum chamber is controlled at 0.5 Pa. Then, the titanium target and the carbon target are turned on for co-sputtering. Under the conditions that the current of the titanium target is 0.5 A, the current of the carbon target is 2.5 A, the applied bias voltage is -150 V, and the bias frequency is 120 kHz, a Ti / DLC composite layer is deposited on the surface of the carbon transition layer by a magnetron sputtering ion plating method, and the thickness of the composite layer is 10 nm; (3) carbon tetrafluoride is introduced into the vacuum chamber, and carbon tetrafluoride is used as the doping gas. The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, a zero bias doping method is selected to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of carbon tetrafluoride is 80 sccm, the ion energy is 400 eV, and the ion beam density is 100 μA / cm 2 , the doping time is 20min, and the deposition rate of fluoride ions is And the thickness of the fluorine layer is 5 nm.
[0064] In combination with all the above embodiments, the implementation process of the present solution is described below through a second specific embodiment, including: (1) placing a cling film in a vacuum chamber, controlling the temperature in the vacuum chamber to be maintained at 35°C, and evacuating the vacuum chamber to 1.0×10 -3Pa or higher vacuum degree, then, introduce argon gas (Ar, purity is 99.99%) into the vacuum chamber, and control the pressure in the vacuum chamber at 0.9 Pa, turn on the carbon target for sputtering, and use magnetron sputtering ion plating method to deposit a carbon transition layer on the surface of the plastic wrap under the conditions of carbon target current of 1.3A, applied bias voltage of -150V, and bias frequency of 180kHz, and the thickness of the carbon transition layer is 20nm; (2) adjust the vacuum degree in the vacuum chamber to 1.5×10 -3 Pa or more, nitrogen (N2, purity of 99.99%) is introduced into the vacuum chamber, and the pressure in the vacuum chamber is controlled at 0.5 Pa. Then, the titanium target and the carbon target are turned on for co-sputtering. Under the conditions of 0.5 A for the titanium target and 2.5 A for the carbon target, a bias voltage of -150 V and a bias frequency of 120 kHz, a Ti / DLC composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating, and the thickness of the composite layer is 13 nm. (3) Carbon tetrafluoride is introduced into the vacuum chamber, and carbon tetrafluoride is used as the doping gas. The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, a zero bias doping method is selected to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of carbon tetrafluoride is 80 sccm, the ion energy is 400 eV, and the ion beam density is 100 μA / cm 2 , the doping time is 20min, and the deposition rate of fluoride ions is And the thickness of the fluorine layer is 5 nm.
[0065] In combination with all the above embodiments, the implementation process of the present solution is described below through the third specific embodiment, including: (1) placing a cling film in a vacuum chamber, controlling the temperature in the vacuum chamber to be maintained at 50°C, and evacuating the vacuum chamber to 1.0×10 -3 Pa or higher vacuum degree, then, introduce argon gas (Ar, purity is 99.99%) into the vacuum chamber, and control the pressure in the vacuum chamber at 1.0 Pa, turn on the carbon target for sputtering, and use magnetron sputtering ion plating method to deposit a carbon transition layer on the surface of the plastic wrap under the conditions of 1.5A current of the carbon target, -150V bias voltage applied, and 180kHz bias frequency, and the thickness of the carbon transition layer is 20nm; (2) adjust the vacuum degree in the vacuum chamber to 1.5×10 -3Pa or more, nitrogen (N2, purity of 99.99%) is introduced into the vacuum chamber, and the pressure in the vacuum chamber is controlled at 0.5 Pa. Then, the titanium target and the carbon target are turned on for co-sputtering. Under the conditions that the current of the titanium target is 0.5 A, the current of the carbon target is 2.5 A, the applied bias voltage is -150 V, and the bias frequency is 120 kHz, a Ti / DLC composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating, and the thickness of the composite layer is 15 nm; (3) carbon tetrafluoride is introduced into the vacuum chamber, and carbon tetrafluoride is used as the doping gas. The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, a zero bias doping method is selected to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of carbon tetrafluoride is 80 sccm, the ion energy is 400 eV, and the ion beam density is 100 μA / cm 2 , the doping time is 20min, and the deposition rate of fluoride ions is And the thickness of the fluorine layer is 5 nm.
[0066] In summary, the coating method for the surface of a cling film provided in an embodiment of the present invention firstly deposits a carbon transition layer on the surface of the cling film by magnetron sputtering ion plating; then deposits a composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating; finally, doping fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer. The embodiment of the present invention performs vacuum coating on the surface of the cling film, so that the coated cling film has the characteristics of being smooth, tight, and non-lipophilic, oxygen molecules cannot penetrate the cling film, and can effectively prevent the packaged objects from being oxidized, thereby extending the preservation time and enhancing the preservation effect.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coating method for the surface of a cling film, characterized in that: include: A carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating; Depositing a composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating; Fluorine ions are doped on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer.
2. The coating method for the surface of the cling film according to claim 1, characterized in that: The method of depositing a carbon transition layer on the surface of the cling film by magnetron sputtering ion plating specifically includes: Place the plastic wrap in the vacuum chamber and evacuate to a vacuum degree of 1.0×10 -3 Pa, and controlling the temperature in the vacuum chamber to be maintained at 20°C to 50°C; Introducing argon gas into the vacuum chamber, and controlling the gas pressure in the vacuum chamber to be between 0.8 and 1.0 Pa; The carbon target is turned on, and a carbon transition layer is deposited on the surface of the cling film by magnetron sputtering ion plating; wherein the current of the carbon target is 1.0-1.5A, the applied bias voltage is -150V, and the bias frequency is 180kHz.
3. The coating method for the surface of the cling film according to claim 2, characterized in that: The thickness of the carbon transition layer is 20 nm.
4. The coating method for the surface of the cling film according to claim 2, characterized in that: The method of depositing the composite layer on the surface of the carbon transition layer by magnetron sputtering ion plating specifically includes: The vacuum degree in the vacuum chamber was adjusted to 1.5×10 -3 Pa, nitrogen is introduced into the vacuum chamber, and the air pressure in the vacuum chamber is controlled at 0.5 Pa; The titanium target and the carbon target are turned on, and a composite layer is deposited on the surface of the carbon transition layer by magnetron sputtering ion plating; wherein the current of the titanium target is 0.5A, the current of the carbon target is 2.5A, the applied bias voltage is -150V, and the bias frequency is 120kHz.
5. The coating method for the surface of the cling film according to claim 4, characterized in that: The thickness of the composite layer is 10-15 nm.
6. The coating method for the surface of the cling film according to claim 4, characterized in that: The step of doping fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer specifically includes: The vacuum degree in the vacuum chamber is 3.5×10 -4 Pa, using carbon tetrafluoride as a doping gas, and adopting a zero bias doping method to dope fluorine ions on the surface of the composite layer to deposit a fluorine layer on the surface of the composite layer; wherein the flow rate of the carbon tetrafluoride is 80sccm, the ion energy is 400eV, and the ion beam density is 100μA / cm 2 .
7. The coating method for the surface of the cling film according to claim 6, characterized in that: The doping time of the fluorine layer is 20 minutes.
8. The coating method for the surface of the cling film according to claim 6, characterized in that: The deposition rate of the fluorine layer is 9. The coating method for the surface of the cling film according to claim 6, characterized in that: The thickness of the fluorine layer is 5 nm.
10. The method for coating the surface of a cling film according to any one of claims 1 to 9, characterized in that: The total thickness of the carbon transition layer, the composite layer and the fluorine layer is 20-50 nm.